2013
DOI: 10.1177/1049732313503907
|View full text |Cite
|
Sign up to set email alerts
|

The Process Leading to Help Seeking Following Childhood Trauma

Abstract: In this article we explore the process leading to help seeking following childhood trauma among women who were currently in treatment. We interviewed 13 participants from six treatment groups for clients exposed to humaninflicted traumas. Transcripts were analyzed using a hermeneutical-phenomenological approach. Help seeking was initiated after a prolonged period of time (13 to 58 years after first trauma exposure), during which participants relied heavily on a strategy of managing on their own. Self-managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Additionally, the present study sheds light on targeting specific contextual and individual factors to ameliorate mothers’ depression and PTSD trajectories as these factors have clinically meaningful impact on treatment seeking (Stige, Træen, & Rosenvinge, 2013) and outcomes (Sayin, Candansayar, & Welkin, 2013). Interventions targeting social support, post-traumatic cognitions, dissociation and shame may aid in increasing mothers’ coping (for a review see Keeshin & Strawn, 2014; Oktedalen et al, 2014) via Interpersonal Therapy (Grigoriadis & Ravitz, 2007), Cognitive Processing Therapy (CPT; Resick et al, 2008), and Dialectical Behavior Therapy (DBT; Harned, Korslund, & Linehan, 2014; Neacsiu, Lungu, Harned, Rizvi, & Linehan, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, the present study sheds light on targeting specific contextual and individual factors to ameliorate mothers’ depression and PTSD trajectories as these factors have clinically meaningful impact on treatment seeking (Stige, Træen, & Rosenvinge, 2013) and outcomes (Sayin, Candansayar, & Welkin, 2013). Interventions targeting social support, post-traumatic cognitions, dissociation and shame may aid in increasing mothers’ coping (for a review see Keeshin & Strawn, 2014; Oktedalen et al, 2014) via Interpersonal Therapy (Grigoriadis & Ravitz, 2007), Cognitive Processing Therapy (CPT; Resick et al, 2008), and Dialectical Behavior Therapy (DBT; Harned, Korslund, & Linehan, 2014; Neacsiu, Lungu, Harned, Rizvi, & Linehan, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Care staff in specialist services are more experienced in meeting the needs of survivors although the majority of the referrals in specialist services are complex and severe (Astbury ). Trauma survivors who make the decision to seek help can no longer manage their problems on their own; the experience of losing control over their symptoms and the negative impact that these have on their significant others often leads them to seek help (Stigne & Rosenvinge ). Indeed, CSA survivors in our study reported elevated levels of a few psychopathological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…How to understand this delay and the mechanisms behind it, however, is not well understood. Interviewing 13 trauma survivors about the process that led them to seek help following childhood trauma provided examples of what mechanisms contributed to delays in help-seeking for these participants-including the interplay between a coping strategy of selfmanagement and situational demands (Stige, Traeen, & Rosenvinge, 2013).…”
Section: The Discovery Functionmentioning
confidence: 99%
“…Moreover, in the design and focus of qualitative research itself, groups that are traditionally 8/21 marginalised can be given a voice. For example, by exploring other-initiated versus self-initiated help-seeking among 13 trauma survivors, it became clear that a praxis of judging motivation and denying health services solely based on the number of previous consultation series ran a high risk of excluding motivated survivors in need of mental health services (Stige et al, 2013). Pugach and Goodman (2015) studied low-income women's experiences in out-patient therapy and showed how we need nuances of understanding to differentiate no-show and attrition that point to low motivation or lack of structure among this population.…”
Section: The Critical Functionmentioning
confidence: 99%